Expressão e localização das proteínas c-Fos e receptor de estrogênio beta no testículo humano - Fabiano Conde Araujo (2006)
The testes are glands with endocrine and exocrine functions, the latter being characterized by sperm formation, or spermatogenesis. This is under the control of a complex system involving endocrine and paracrine signalization. In view of an interrelationship between the expression of c-Fos and estrogen receptor beta (ERbeta) proteins, this investigation evaluated the expression of the protooncogene c-fos and the immunolocalization of c-Fos, phosphorylated c-Fos and ERbeta proteins in the human testis. Testis tissue was obtained from 12 men undergoing orchiectomy as a treatment for prostate cancer. These patients had received no hormonal, chemo or radiation therapy before the operations. Tissues were stained by immunohistochemistry using the avidin-biotin-peroxidase method, and c-fos RNAm expression was assessed with reverse transcriptase- polymerase chain reaction (RT-PCR). The protooncogene c-fos was expressed in the human testis and both forms of c-Fos proteins were immunoreactive, mainly in germ cells (spermatogonia, spermatocytes and spermatids) and Sertoli cells. ERbeta was primarily present in somatic cells (Leydig, Sertoli and myofibrillar cells). Based on these results, we hypothesized two mechanisms for estrogen actions over spermatogenesis. The first would be mediated by Sertoli cells, where estrogens could alter either gene expression or the transcriptional activity of c-Fos protein. The other is an indirect mechanism, representing the interrelationship between somatic and germ cells. Somatic cells, under estrogen influence, could modify germ cell functions by paracrine/juxtacrine factors, which would change gene expression or the transcriptional activity of c-Fos protein.